Controlling Diffusion by Varying Width of Layers in Nano Channel - Goyal, Ishu; Srivastava, Sunita; Tankeshwar, K. (Nano-Micro Letters, 2012)
Diffusive dynamics of fluid forming layers of high and low density regions in a nanochannel has been investigated. Diffusion coefficient in direction parallel and perpendicular to the confining wall has been found to show behaviour which is not observed in micro channel or bulk systems. The behaviour of diffusion is found to be controlled by the width of layers formed in nanochannel due to wall and particle interactions. This is an important result as width of layers and hence flow of fluid inside nano pores/tube can be controlled by an external source.